Avaliação do potencial antioxidante e antimicrobano de extratos de Marcela (Achyrocline satureioides) e capim-limão (Cymbopogon citratus) e aplicação em linguiça frescal - Boeira, Caroline Pagnossim (2018)
Sausage is a meat product which, because of its high fat content, the nature of the raw materials and the lack of heat treatment, is prone to deterioration, lipid oxidation and microbial contamination. Several studies have been carried out in the area of food for the development of plant extracts that exhibit antimicrobial and / or antioxidant properties. The objective of the present study was to obtain extracts of marcela (Achyrocline satureioides) and lemon grass (Cymbopogon citratus), to evaluate antioxidant and antimicrobial capacity, as well as to extract the extract of each herb with higher antioxidant activity in chicken sausages, aiming its natural antioxidant potential. The extracts were obtained by conventional method and ultrasound, at different temperatures (20 °C, 40 °C and 60 °C) for 20 minutes. In the extracts were carried out the analyzes of total phenolics, total flavonoids, antioxidant activity by DPPH, FRAP, ORAC and antimicrobial activity. The extract of lemon grass obtained by the conventional method at 60 °C and the extract of marcela obtained by the ultrasound method at 60 °C were the ones that presented the best antioxidant characteristics and antimicrobial activity, being thus different concentrations of each extract (0,5% and 1,0%) were applied in chicken sausage. The analyzes performed in the sausages were: centesimal composition, pH, water activity, color, lipid oxidation, microbiological and sensorial analyzes. The results obtained in the centesimal composition showed that the sausages are in accordance with the Standard of Identity and Product Quality. Microbiological analyzes for Staphylococcus coagulase positive, Coliformes at 45 °C, Samonella sp and Clostridium sulfite reductant of the products are in accordance with RDC n° 12 of January 2, 2001. The pH and water activity of the sausages of chicken presented a slight increase at the end of storage time. The parameter b * shows that T1 and T2 treatments presented the highest lipid oxidation in agreement with TBARS data. At the end of the 42 days of storage, the TBARS values for the treatment with addition of synthetic antioxidant were 0.99 mg of malondialdeído (MDA) / kg while the added treatments of marcela extract and lemon grass remained below 0, 4 mg of MDA / kg. The sausage added was 1,0% of lemon grass which presented lower lipid oxidation over the 42 days of storage. The sensorial characteristics were maintained, demonstrating good acceptability by the tasters. The results of check-all-which-apply (CATA) showed that the treatments with 1,0% of marcela extract and 0,5 and 1,0% of lemon grass extracts were the groups that received the best sensory attributes, being the most accepted.